Ethics in practice : an anthology - LaFollette, Hugh, 1948- (New Jersey : Wiley., 2020)
"This anthology seeks to provide engagingly written, carefully argued philosophical essays on a wide range of important, contemporary moral issues. When I had trouble finding essays that suited those purposes, I commissioned new ones - twelve for this edition. I also invited a number of philosophers to revise their "classic" essays - seven for this edition. Altogether, well over half of the essays herein were written or revised specifically for Ethics in Practice. This edition includes five introductory essays, including a new one entitled "The Basics of Argumentation.""--
Includes bibliographical references and index.
Keywords: Applied ethics; Ethical problems